RADIOGRAPHIC BONE FORMATION AFTER INDIRECT SINUS LIFT USING TRANSCRESTAL OSTEOTOMY WITH SIMULTANEOUS IMPLANT PLACEMENT - Gada, Sneha; Nessappan, Thyianeswaran; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Dental implants really has transformed the reconstruction and strategic planning of fixed prosthodontics in edentulous posterior maxilla. Increased bone volume via elevation of sinus membrane enables dental implants to be positioned in dysplastic maxillary ridges. The purpose of the research was to determine retrospectively the volume of hard tissue height acquired through a transcrestal method to sinus lifting utilizing osteotomes, together with the concurrent positioning of implants. Documents from the previous 2-year span of partially edentulous cases checked at Saveetha Dental Hospital were searched for patients undergoing implantation to substitute teeth missing in posterior edentulous maxillary area with inadequate vertical osseous height. The inclusion criterion, sinus lift operation, were performed without bone grafts. A maximum of 42 people were selected. Among these patients, 35 were classified as cases recommended for indirect sinus lift while 45 were given implants. The implants being used are 3.5 mm or 4.5 mm diameter and 10.5, 11- or 13-mm length. The average survival rate for implants was 97.78 per cent. The mean bone height estimated from alveolar crest to the base of implant just at time of implantation was 6.79 mm ± 1.35 mm. Measured mean bone height at six-month follow-up period was 11.4 mm ±0.88 mm, which was significant (p < 0.05). Trans crestal osteotomy with implants tenting sinus membrane without extra graft material might show a substantial mean osseous height increase of 4.6 mm.